Relationship between brain activity, cognitive function, and sleep spiking activation in new-onset self-limited epilepsy with centrotemporal spikes - Li, Yanzhang; Li, Yihan; Sun, Jintao; Niu, Kai; Wang, Pengfei; Xu, Yue; Wang, Yingfan; Chen, Qiqi; Zhang, Ke; Wang, Xiaoshan (Frontiers in Neurology, 2022)
Objective: This study aimed to investigate the relationship between cognitive function sleep spiking activation and brain activity in self-limited epilepsy with centrotemporal spikes (SeLECTS). Methods: We used spike-wave index (SWI), which means the percentage of the spike and slow wave duration to the total non-REM (NREM) sleep time, as the grouping standard. A total of 14 children with SeLECTS (SWI≥50%) , 21 children with SeLECTS (SWI＜50%), and 20 healthy control children were recruited for this study. Cognitive function was evaluated using the Wechsler Intelligence Scale for Children, Fourth Edition (Chinese version) (WISC-IV). Magnetic source activity was assessed using magnetoencephalography calculated for each frequency band using the accumulated source imaging (ASI) technique. Results: Children with SeLECTS (SWI≥50%) had the lowest cognitive function scores, followed by those with SeLECTS (SWI＜50%) and then healthy controls. There were significant differences in the localization of magnetic source activity between the three groups: in the alpha (8–12 Hz) frequency band, children with SeLECTS (SWI≥50%) showed deactivation of the medial frontal cortex (MFC) region; in the beta (12–30 Hz) frequency band, children with SeLECTS (SWI≥50%) showed deactivation of the posterior cingulate cortex (PCC) segment; and in the gamma (30–80 Hz) frequency band, children in the healthy group showed activation of the PCC region. Conclusion: This study revealed significant decreases in cognitive function in children with SeLECTS (SWI≥50%) compared to children with SeLECTS (SWI＜50%) and healthy children, as well as significant differences in magnetic source activity between the three groups. The findings suggest that deactivation of magnetic source activity in the PCC and MFC regions is the main cause of cognitive function decline in SeLECTS patients with some frequency dependence.